Identifying the poor and the needy among the beneficiaries of zakat: Need for a zakat-based poverty threshold in Nigeria - Ahmed, BO; Johari, F; Wahab, KA (Emerald Group Publishing Ltd., 2024)
Indexed by WOS/SCOPUS